Optimizing Empirical Antibiotic Therapy in Febrile Pediatric Oncology Patients through a Clinical Decision Pathway - Yamileth Arellano; Martha Avilés Robles; Fernando Ríosvelasco (Journal of the Pediatric Infectious Diseases Society, 2026)
Abstract Background Timely management of a child with cancer and fever (CCF) requires accurate evaluation and appropriate antibiotic selection to prevent infectious complications. Clinical decision tools, such as Clinical Decision Pathways (CDPs), are increasingly adopted in healthcare systems for their ability to standardize and optimize clinical practice. The aim of this study was to assess the effectiveness and utility of an adapted CDP for initial antibiotic selection in children with cancer and fever. Methods We conducted a prospective observational quality-improvement study at the Hospital Infantil de México Federico Gómez (Mexico City) from September 2024 to October 2025. Patients under 18 years of age with cancer and fever who were managed using the CDP were included. We assessed treatment success, the proportion of cases requiring antibiotic change, and both treatment duration and hospital length of stay (LOS). Group comparisons were performed using the nonparametric Wilcoxon rank-sum test. Physician satisfaction with the CDP was evaluated through a survey, and results were expressed as response percentages. The study was approved by the local research ethics committee. Results A total of 80 febrile episodes in pediatric cancer patients were analyzed using the CDP. Males represented 52% of cases, and the median age was 9 years (IQR: 6–13). Acute lymphoblastic leukemia was the most frequent malignancy (61%), and the most common infectious focus was abdominal (20%). Cefepime was the initial antibiotic in 64% of cases. In 89% (n = 71), the CDP guided an appropriate initial antibiotic selection, while 11% required a change due to treatment failure. No significant difference was found in antibiotic treatment duration between groups (z = –0.887; p = 0.375). Conversely, LOS was significantly longer in patients requiring antibiotic change (median 16 days [IQR 14–17]) compared to those who did not (median 8 days [IQR 7–11]; z = –2.308; p = 0.021). Overall, 91.5% of healthcare providers agreed that the CDP improves the quality of care for children with cancer and fever. Conclusion The implementation of a CDP for antibiotic selection in children with cancer and fever proved effective in standardizing empirical treatment and reducing hospital stay. Physician acceptance was high, highlighting the tool’s clarity, ease of use, and positive impact on care quality.